Advanced credit risk analysis and management : an indispensable book on credit and finance for better risk management - Joseph, Ciby, 1969- (Chichester, West Sussex : John Wiley & Sons Inc., 2013)
Credit is essential in the modern world and creates wealth, provided it is used wisely. The Global Credit Crisis during 2008/2009 has shown that sound understanding of underlying credit risk is crucial. If credit freezes, almost every activity in the economy is affected. The best way to utilize credit and get results is to understand credit risk. Advanced Credit Risk Analysis and Management helps the reader to understand the various nuances of credit risk. It discusses various techniques to measure, analyze and manage credit risk for both lenders and borrowers. The book begins.
pt. I. Introduction -- pt. II. Firm (or) obligor credit risk -- pt. III. Credit risks : project and working capital -- pt. IV. Credit portfolio risks -- pt. V. Portfolio risk mitigants -- pt. VI. Credit risk pricing -- pt. VII. The last line of defence : security -- pt. VIII. Credit crisis.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Credit -- Management; Risk management; BUSINESS & ECONOMICS -- Investments & Securities -- General; Credit -- Management; Risk management; Electronic books; Electronic books; Electronic books